Giant dielectric behavior of bafe0.5nb0.5o3perovskite ceramic - Uraiwan Intatha (2018)
© 2009 by World Scientific Publishing Co. Pte. Ltd. All rights reserved. Single-phase cubic Ba(Fe, Nb)0:5O3 (BFN) powder was synthesized by solid-state reac- tion at 1443 K for 4 hour in air. X-ray diαraction indicated that the BFN oxide mixture calcined at 120C crystallizes to the pure cubic perovskite phase. BFN ceramics were produced from this powder by sintering at 1623-1673 K for 4 hrs in air. Samples prepared under these conditions achieved up to 94.7% of the theoretical density. The temperature dependence of their dielectric constant and loss tangent, measured at diαerence frequen-cies, shows an increase in the dielectric constant with temperature which is probably due to disorder on the B site ion of the perovskite. Non-Debye type of relaxation phenom- ena has been observed in the BFN ceramics as cormed by Cole-Cole plots. The higher value of 0 at the lower frequency is explained on the basis of the Maxwell{Wagner (MW) polarization model